DNA fingerprinting and assessment of some physiological changes in Al-induced Bryophyllum daigremontianum clones - VARDAR, FİLİZ; ÖZYİĞİT, İBRAHİM İLKER (SPRINGER, 2019)
Aluminum (Al) is one of the most important stress factors that reduce plant productivity in acidic soils. Present work thereby analyzed Al-induced genomic alterations in Bryophyllum daigremontianum clones using RAPD and ISSR markers, and investigated responding changes in photosynthetic pigment (chlorophyll a, b, a/b, total chlorophyll and carotenoid) contents and total soluble protein amounts in plant leaves. The main reason for the use of bulbiferous spurs originated clone plants was to increase reliability and acceptability of RAPD and ISSR techniques in DNA fingerprinting. Raised 40 clone plants were divided into five separate groups each with eight individuals and each experimental group was watered with 0 (control), 0 (acid control), 50, 100 and 200 mu M AlCl3-containing Hoagland solutions on alternate days for two and a half months. All plant soils except control group were sprayed with 0.2% sulfuric acid following watering days and this contributed acidic characteristic (pH 4.8) to soil structure. Increase in Al concentrations were accompanied by an increase in total soluble protein amounts, a decrease in photosynthetic pigment contents, and with appearance, disappearance and intensity changes at RAPD and ISSR band profiles. Out of tested RAPD1-25 and ISSR1-15 primers, RAPD8, RAPD9, ISSR2 and ISSR7 primers produced reproducible band profiles that were distinguishable between treatment and control groups. Findings showed that RAPD and ISSR fingerprints have been useful biomarkers for investigation of plant genotoxicity, especially in clone plants. Moreover, if these fingerprints are integrated with other physiological parameters they could become more powerful tools in ecotoxicology.
Keywords: RAPD; ISSR; Clone plant; Genotoxicity; Acidic soil; DNA fingerprinting; AMPLIFIED POLYMORPHIC DNA; PROGRAMMED CELL-DEATH; GENOMIC TEMPLATE STABILITY; ALUMINUM TOXICITY; OXIDATIVE STRESS; ABIOTIC STRESS; PLANT; TOLERANCE; GROWTH; ACCUMULATION